Household economic impact of HIV‐associated cryptococcal meningitis in five countries in Southern and Eastern Africa - David S. Lawrence; Charles Muthoga; Jack Adams; Antoinette Buhle Ndweni; David R. Boulware; Chimwemwe Chawinga; Kyla Comins; Eltas N. Dziwani; Admire Hlupeni; Mina C. Hosseinipour; Samuel Jjunju; Cecilia Kanyama; et al. (Journal of the International AIDS Society)
Abstract Introduction HIV‐associated cryptococcal meningitis is the second leading cause of AIDS‐related mortality. Cryptococcal meningitis is a poverty‐related disease and the majority of cases occur in settings where resources are limited and access to quality care is often linked to an individual's ability to pay for services. We have previously demonstrated the efficacy, safety and cost‐effectiveness of a single, high‐dose liposomal amphotericin‐based treatment regimen within the AMBITION‐cm trial. Here, we present a five‐country, within‐trial analysis exploring the household economic impact of cryptococcal meningitis. Methods Eight hundred and ten participants were recruited into this sub‐study in Botswana, Malawi, South Africa, Uganda and Zimbabwe between January 2018 and February 2021. We collected data on annual household expenditure, direct costs and indirect costs incurred prior to enrolment and during the 10‐week trial period. Costs were inflated and converted to 2022 USD. We calculated out‐of‐pocket expenditure, lost income and catastrophic healthcare expenditure, defined as costs exceeding 20% of annual household expenditure. Results The average total out‐of‐pocket expenditure plus lost income prior to enrolment was $132 and 17.9% (145/810, 95% CI 15.3–20.5) of participant households had already experienced catastrophic healthcare expenditure. Among the 592 surviving participants, when combining out‐of‐pocket expenditure and lost income, the average cost was $516 and 29.1% of annual household expenditure across all countries, ranging from $230 (7.6%) in South Africa to $592 (64.2%) in Zimbabwe. More than half (296/581, 51.0%, 95% CI 46.9–55.0) of households experienced catastrophic healthcare expenditure by the end of the trial, ranging from 16.0% (13/81, 95% CI 7.9–24.2) in South Africa to 68.1% (156/229, 95% CI 62.0–74.2) in Uganda. Conclusions This is the first study exploring the household economic impact experienced by those diagnosed with cryptococcal meningitis. The household economic impact of cryptococcal meningitis is high and more than half of households of individuals who survive experience catastrophic healthcare expenditure. It is likely these figures are higher outside of the research setting. This highlights the profound financial impact of this devastating infection and provides a rationale to offer financial and social protection to those affected. Trial Registration Number ISRCTN72509687